Special child, special mother: the sense of strength in mothers of children with congenital zika virus syndrome - Hamad,Graziela Brito Neves Zboralski (2019)
Abstract Objectives: To understand the meanings of having a child with the Congenital Zika virus Syndrome in the experience of women and, from this, what they would say to others who find themselves in the same situation. Method: Qualitative and interpretive study, based on the Model of Resilience, Stress, Adjustment and Family Adaptation proposed by McCubbin and McCubbin. 40 mothers from different cities in the state of Paraiba took part in the study. Results: The meanings found were classified in three thematic categories: the divine force that transforms life of the mothers; patience and love, double feelings as a source of overcoming; and the sense of mother’s strength beyond the disease. Conclusion and implication for practice: Caring for a child diagnosed with Congenital Zika virus Syndrome has involved emotional, social, spiritual and economic aspects, as well as a transformation and suffering process. The experiences may contribute to the qualification of healthcare professionals who deal directly with these mothers, and possibly, favor the confrontation and adaptation of them and their families and of the new families that may come to have children with